Physician Survey of Practices on Diet, Physical Activity and Weight Control: Questionnaire on Adult Care – validation of the Polish language version of the questionnaire - Hubert-Lutecka, Agnieszka; Bartusik-Aebisher, Dorota; Żal, Marcin; Binkowska-Bury, Monika (European Journal of Clinical and Experimental Medicine, 2018)
<p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. According to the World Health Organization, non-infectious chronic diseases will become the leading cause of disability by 2020 and can be the most expensive health problem. Type 2 diabetes, hypertension, smoking, poor eating habits, insufficient physical activity and the resulting overweight and obesity are among the main modifiable factors of non-infectious chronic diseases. The results of epidemiological studies indicate that the prevalence of these factors in the Polish population is constantly growing, which is associated with the dissemination of unfavorable eating habits and sedentary lifestyle. Their combating and preventive and educational activities of patients in the scope of modifiable lifestyle behaviors related to lifestyle should be implemented primarily through primary care physicians. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. To validate the Polish language version of Physician Survey of Practices on Diet, Physical Activity and Weight Control: Questionnaire on Adult Care. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A Polish version of the questionnaire “Physician Survey of Practices on Diet, Physical Activity and Weight Control: Questionnaire on Adult Care” was created. Validation was carried out on a group of 30 primary care physicians. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Very good results in terms of internal coherence of the questionnaire were obtained - the Alpha-Crombach coefficient was 0.82. The level of reproducibility was established with an ICC factor, which was 0.81. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The tested Polish version of the questionnaire can be used to conduct research among primary care physicians in Poland.